2017
DOI: 10.18632/oncotarget.16523
|View full text |Cite
|
Sign up to set email alerts
|

iNOS-derived nitric oxide promotes glycolysis by inducing pyruvate kinase M2 nuclear translocation in ovarian cancer

Abstract: Aerobic glycolysis is essential for tumor growth and survival. Activation of multiple carcinogenic signals contributes to metabolism reprogramming during malignant transformation of cancer. Recently nitric oxide has been noted to promote glycolysis but the mechanism remains elusive. We report here the dual role of nitric oxide in glycolysis: low/physiological nitric oxide (≤ 100 nM) promotes glycolysis for ATP production, oxidative defense and cell proliferation of ovary cancer cells, whereas excess nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…The ability of high levels of NO to reduce colony formation has been previously observed [41]. Although the underlying molecular mechanisms for this effect are still being elucidated, it is known that excess NO impedes epidermal growth factor receptor/extracellular signal regulated kinase 2 (EGFR/ERK2)-dependent nuclear translocation of pyruvate kinase M2 (PKM2), thereby inhibiting glycolysis and inducing cell death [41,42]. It is also known that various NO-donor treated malignancies and macrophages have shown increased p53 expression, which led to apoptosis [35,36].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The ability of high levels of NO to reduce colony formation has been previously observed [41]. Although the underlying molecular mechanisms for this effect are still being elucidated, it is known that excess NO impedes epidermal growth factor receptor/extracellular signal regulated kinase 2 (EGFR/ERK2)-dependent nuclear translocation of pyruvate kinase M2 (PKM2), thereby inhibiting glycolysis and inducing cell death [41,42]. It is also known that various NO-donor treated malignancies and macrophages have shown increased p53 expression, which led to apoptosis [35,36].…”
Section: Discussionmentioning
confidence: 78%
“…These experiments showed that after 24 h of exposure to GSNO, 21-24% of cells were no longer metabolically active and 100% were incapable of colony formation. The ability of high levels of NO to reduce colony formation has been previously observed [41]. Although the underlying molecular mechanisms for this effect are still being elucidated, it is known that excess NO impedes epidermal growth factor receptor/extracellular signal regulated kinase 2 (EGFR/ERK2)-dependent nuclear translocation of pyruvate kinase M2 (PKM2), thereby inhibiting glycolysis and inducing cell death [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Carboxyl terminus of Hsc70-interacting protein (CHIP), an E3 ligase, inhibits aerobic glycolysis progression of ovarian carcinomas through CHIP-mediated PKM2 degradation 142 . iNOS/NO promotes glycolysis via inducing PKM2 nuclear translocation 143 . Mitochondrial calcium uptake 1 (MICU1) increases aerobic glycolysis and chemoresistance in ovarian cancer 144 .…”
Section: Other Regulatorsmentioning
confidence: 99%
“…In ovarian cancer cells, the researchers found that NO has dual biological functions in tumour cells, and low concentration of NO promoted the glycolysis while inhibits the glycolysis at high concentrations. The iNOS induced by LPS can enhance the glycolysis in ovarian cancer cells, and the levels of iNOS mRNA can predict the poor prognosis in the patients of ovarian cancer (Li et al., ). Therefore, NO was quite complex in tumour cells, and NOS/NO has a dual role in carcinogenesis, progression and treatment by NO concentration and exposure time dependence, NOS isomers and tumour microenvironment and other factors (Lala & Chakraborty, ).…”
Section: Discussionmentioning
confidence: 99%